Scoring of Programmed Death-Ligand 1 Immunohistochemistry on Cytology Cell Block Specimens in Non–Small Cell Lung Carcinoma: An Interobserver Agreement Study. Issue 4 (26th June 2020) - Hernandez, Andrea; Brandler, Tamar C; Chen, Fei; Zhou, Fang; Xia, Yuhe; Zhong, Judy; Moreira, Andre L; Simms, Anthony; Sun, Wei; Wei, Xiao Jun; Simsir, Aylin
Abstract: Objectives: Recent investigations have shown strong correlations between cytology and surgical non–small cell lung carcinoma (NSCLC) specimens in programmed death-ligand 1 (PD-L1) immunohistochemical (IHC) evaluations. Our study aims to evaluate the reproducibility of PD-L1 IHC scoring in NSCLC cytology cell blocks (CBs) and to assess the impact of CB cellularity, method of sample collection, and observer subspecialty on scoring agreement. Methods: PD-L1 IHC was performed on 54 NSCLC cytology CBs and was scored independently by seven cytopathologists (three of seven with expertise in pulmonary pathology). Three-tier scoring of negative (<1%), low positive (1%-49%), and high positive (≥50%) and interrater agreement were assessed. Results: Total and majority agreement among cytopathologists was achieved in 48% and 98% of cases, respectively, with κ = 0.608 (substantial agreement; 95% confidence interval, 0.50-0.72). Cytopathologists with pulmonary pathology expertise agreed in 67% of cases (κ = 0.633, substantial agreement), whereas the remaining cytopathologists agreed in 56% of cases (κ = 0.62, substantial agreement). CB cellularity ( P = .36) and sample collection type ( P = .59) had no statistically significant difference between raters. Conclusions: There is substantial agreement in PD-L1 IHC scoring in cytology CB specimens among cytopathologists. Additional expertise in pulmonary pathology, sample collection type, and CB cellularity have no statistically significant impact on interobserver agreement.